Portraits of Arnold O. Beckman (1900-2004) - Hesketh, Dean D.; Healy, Dale; Laursen, Rene; Dietrich, T. A. (1963)
Dr. Arnold O. Beckman (1900-2004) invented the first commercially successful electric pH meter in 1934 and thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation.
Keywords: Scientists--Portraits; Beckman, Arnold O.; Portraits; Portraits, American